Bovine Protein C Inhibitor Has a Unique Reactive Site and Can Transiently Inhibit Plasmin - Yuasa, Hiroyuki; Tanaka, Hitoshi; Hayashi, Tatsuya; Wakita, Toshiaki; Nakamura, Hideaki; Nishioka, Junji; Kawarada, Yoshifumi; Suzuki, Koji (Thrombosis and Haemostasis, 2000)
Protein C inhibitor (PCI) regulates the anticoagulant protein C pathway by neutralizing activated protein C and thrombin-thrombomodulin complex in the human hemostatic system. In this study, we cloned a full-length bovine PCI cDNA encoding a putative 19-residue signal peptide and a 385-residue mature protein; this showed 70.6%, 70.6%, 57.5% and 59.6% amino acid sequence homology with the human, rhesus monkey, rat and mouse PCIs, respectively. Bovine PCI mRNA (2.1 kb in size) was expressed strongly in the liver, and moderately in the kidney and testis, but not in other tissues tested. Bovine PCI has a putative reactive site peptide bond, Lys-Ser, that is different from the reactive site sequence (Arg-Ser) of other species’ PCI. We found that bovine PCI transiently inhibits bovine plasmin, but not human plasmin. Western blot analysis showed that the reactive site of bovine PCI is cleaved during the course of complex formation with bovine plasmin; degraded PCI is released from the complex gradually concomitant with the recovery of plasmin activity. These findings suggest that bovine PCI plays a role not only in the protein C pathway but also in the fibrinolytic activity of bovine hemostatic system.Abbreviations: PCI, protein C inhibitor, Serpin, serine protease inhibitor, APC, activated protein C, TM, thrombomodulin.
Keywords: Protein C inhibitor; serine protease inhibitor; species specificity; plasmin inhibitor; fibrinolysis